Six Teacher Methods in Shaping Santri Morals in Boarding School - Intan Fuadi Hasibuan; Fuady Anwar (International Journal of Multidisciplinary Research of Higher Education, 2023)
This study aims to determine the coaching method used by the teacher in shaping the morals of the students at Madrasah Diniyah Takmiliyah Awaliyah Baitul Makmur Padang. Sources of data were taken from six informants through in-depth interviews who were selected using purposive sampling technique. The six informants consisted of three coaches and three students. All the results of the interviews were then analyzed systematically through four steps of analytical activities, namely (data collection, data reduction, presentation and drawing conclusions). Overall the results of the analysis show; Regarding the coaching method used by the teacher in instilling morals in students by using six methods, namely, i) discussion ii) story iii) advice iv) exemplary v) habituation vi) punishment. The results of this study can be used as initial data for future research in examining different issues related to this problem and other issues relevant to this context.